2020
DOI: 10.1016/j.ymthe.2020.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Opa1 Overexpression Protects from Early-Onset Mpv17−/−-Related Mouse Kidney Disease

Abstract: Moderate overexpression of Opa1 , the master regulator of mitochondrial cristae morphology, significantly improved mitochondrial damage induced by drugs, surgical denervation, or oxidative phosphorylation (OXPHOS) defects due to specific impairment of a single mitochondrial respiratory chain complex. Here, we investigated the effectiveness of this approach in the Mpv17 −/− mouse, characterized by profound, multisystem mitochondrial DNA (mtDNA) depletio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
7
1
Order By: Relevance
“…Subsequently, using a gold-labeled technique, the expression of OPA-1, HDHD-3, and Nrf-2 in renal and hepatic mitochondria was evaluated in this study. In a mouse model, the increase of OPA-1, a master regulator of mitochondrial cristae morphology, reduces mitochondrial damage from various causes, including mitochondrial DNA depletion-induced glomerulosclerosis [ 26 ] and sorafenib-induced (an anticancer agent) hepatocyte apoptosis [ 27 ]. In liver mitochondria treated with a high dose of PQ, our research revealed a downregulation of OPA-1, whereas renal mitochondria tended to exhibit a slight upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, using a gold-labeled technique, the expression of OPA-1, HDHD-3, and Nrf-2 in renal and hepatic mitochondria was evaluated in this study. In a mouse model, the increase of OPA-1, a master regulator of mitochondrial cristae morphology, reduces mitochondrial damage from various causes, including mitochondrial DNA depletion-induced glomerulosclerosis [ 26 ] and sorafenib-induced (an anticancer agent) hepatocyte apoptosis [ 27 ]. In liver mitochondria treated with a high dose of PQ, our research revealed a downregulation of OPA-1, whereas renal mitochondria tended to exhibit a slight upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…SYM1, the yeast ortholog of MPV17, exhibits strong evolutionary conservation as its depletion can be complemented by human MPV17 expression which can rescue the impaired OXPHOS activity and growth defect under non-fermentable condition (Dallabona et al, 2010). SYM1 depletion leads to mitochondrial ultrastructure defects (Dallabona et al, 2010), as also observed in glomeruli cells of MPV17 -/--related kidney disease mouse model (Luna-Sanchez et al, 2020) and in mpv17 -/zebrafish larvae muscle (Bian et al, 2021). The maintenance of the mitochondrial ultrastructure is mainly achieved by the MItochondrial contact site and Cristae Organizing System (MICOS) complex, which is part of the Mitochondrial Intermembrane space Bridging (MIB) supercomplex.…”
Section: Introductionmentioning
confidence: 94%
“…The MICOS complex is involved in the cristae formation and cristae junction stabilization and bridges the outer and inner membranes of mitochondria, by the interaction with the SAM50 outer membrane complex (reviewed in Kozjak-Pavlovic, 2017). Interestingly, MICOS disassembly and destabilization of the mitochondrial ultrastructure were reported in glomeruli cells from MPV17 -/mouse model, and OPA1 overexpression restored the mtDNA depletion observed in those cells (Luna-Sanchez et al, 2020). Additionally, MPV17 co-immunoprecipitates with the MICOS complex as well as with components of the ATP synthase complex and the membrane Permeability Transition Pore (mPTP) in mouse cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
“…MPV17 protein and its mouse (Mpv17), zebrafish (tra/Mpv17) and Saccharomyces cerevisie (Sym1) orthologs show a high degree of conservation [6]. MPV17 takes part within a high molecular weight complex [7,8] and forms a non selective channel in the IMM affecting mitochondrial membrane potential, reactive oxygen species (ROS) production and cristae formation [7,[9][10][11]. However, the physiological role of the channel and the nature of the cargo remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic strategies with potential general applicability to several mitochondrial diseases have been proposed (reviewed in [15,16]). An effective strategy against the deleterious role of cristae disruption in mitochondrial pathogenic mechanisms has been successfully exploited in a mouse [11], thanks to a moderate overexpression of Opa1 [17], a master regulator of shape and function of mitochondrial cristae.…”
Section: Introductionmentioning
confidence: 99%